Implementation of E-Service Quality at Front Office Department to Increase Guest Satisfaction - Ni Made Nitha Balistha; I Ketut Sutama; Ida Ayu Elistyawati; I Gede Mudana; Ni Nyoman Triyuni; Ni Made Ernawati (International Journal of Travel, Hospitality and Events, 2022)
Purpose: The purpose of this research is to know the implementation of e-service quality Front Office Department in increasing guest satisfaction at a 5-star hotel located in Ubud, Bali. Research methods: The data analysis techniques used in this research are servqual (service quality) and IPA (Importance Performance Analysis). Results and discussions: The results of the research from servqual (service quality) show that the positive servqual score gap is more than the negative servqual score gap, where overall the e-service quality implemented at the hotel has provided satisfaction to guests and showed good service. Meanwhile, the results of the IPA (Importance Performance Analysis) research show that indicators that need to be improved are the availability of products displayed on electronic media (Q6) and consumer personal data protected on electronic media (Q7). Implication:  indicators that need to be maintained in this research are information related to credit cards or payments that can be guaranteed security carried out by FO Staff (Q8), FO Staff handle guest complaints quickly and swiftly (Q9), Hotels have a refund mechanism (refunds). for payment transactions (Q10) and the hotel has 24 hours customer service by the FO Staff (Q11).   Keywords: E-service quality, guest satisfaction, front office department.